Effects of extreme floods on macroinvertebrate assemblages in tributaries to the Mohawk River, New York, USA - Calderon, Mirian Roxana (2017)
Climate change is forecast to bring more frequent and intense precipitation to New York which has motivated research into the effects of floods on stream ecosystems. Macroinvertebrate assemblages were sampled at 13 sites in the Mohawk River basin during August 2011, and again in October 2011, following historic floods caused by remnants of Hurricane Irene and Tropical Storm Lee. The annual exceedance probabilities of floods at regional flow-monitoring sites ranged from 0.5 to 0.001. Data from the first 2 surveys, and from additional surveys done during July and October 2014, were assessed to characterize the severity of flood impacts, effect of seasonality, and recovery. Indices of total taxa richness; Ephemeroptera, Plecoptera, and Trichoptera (EPT) richness; Hilsenhoff's biotic index; per cent model affinity; and nutrient biotic index-phosphorus were combined to calculate New York State Biological Assessment Profile scores. Analysis of variance tests were used to determine if the Biological Assessment Profile, its component metrics, relative abundance, and diversity differed significantly (p ≤.05) among the four surveys. Only total taxa richness and Shannon–Wiener diversity increased significantly, and abundance decreased significantly, following the floods. No metrics differed significantly between the July and August 2014 surveys which indicates that the differences denoted between the August and October 2011 surveys were caused by the floods. Changes in taxa richness, EPT richness, and diversity were significantly correlated with flood annual exceedance probabilities. This study increased our understanding of the resistance and resilience of benthic macroinvertebrate communities by showing that their assemblages were relatively impervious to extreme floods across the region.